The short-term economic influence analysis of government regulation on railway freight transport in continuous time. - Jingwei Guo; Jiayi Guo; Tingyue Kuang; Yimin Wang; Wenxin Li (PLoS ONE)
Regulatory impact analysis, a crucial aspect of the development of railway transportation in China, has faced increasing challenges due to the complex nature of the transportation system and various influencing factors. This study proposes an improved comparative static model (ICSM) that intelligently integrates recursive principles and the Laplace transform to estimate the impact of macroeconomic policy reforms on the economic variables of China Railway Corporation (CRC). The ICSM integrates recursive principles and Laplace transform to solve complex conditions of eigenvalues as multiple roots and a coefficient matrix unable to diagonalize in the ICSM. Additionally, the paper discusses the government's potential impact on variables such as freight and labor after reform and highlights the sensitivity of tax policy compared to investment subsidies in the short term. The findings provide theoretical and methodological support for optimizing railway freight management during the reform process and can serve as a reference for temporary economic policy adjustments.